Pengaruh Crowe’s Fraud Pentagon Theory sebagai Uji Identifikasi terhadap Fraudulent Financial Statement : Studi Empiris pada Perusahaan Manufaktur Sub Industri Makanan dan Minuman yang Terdaftar pada Bursa Efek Indonesia Periode 2019-2023 - Aldi Rozani; Prita Andini (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
The purpose of this research is to find the influence of financial target variables, ineffective monitoring, change in auditor, change in director, frequent number of CEO's picture on fraudulent financial statements. The sample in this study includes 45 food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the period (2019-2023). The sampling technique used the purpose sampling method and obtained 225 sample data from 45 companies. The statistical analysis used in this research is logistic regression analysis using the Statistical Product and Service Solution (SPSS) Program Version 22. The results of this research show that financial targets have a negative and significant effect on fraudulent financial statements, ineffective monitoring has an insignificant effect on fraudulent financial statements. statement, change in auditor has no significant effect on fraudulent financial statements, change in director has no significant effect on fraudulent financial statements, frequent number of CEO picture has a negative and significant effect on fraudulent financial statements.